Design, synthesis, and in vitro bioactivity evaluation of fluorine-containing analogues for sphingosine-1-phosphate 2 receptor. Issue 16 (15th August 2019) - Luo, Zonghua; Liu, Hui; Klein, Robyn S.; Tu, Zhude
Graphical abstract: Abstract: Twenty eight new aryloxybenzene analogues were synthesized and their in vitro binding potencies toward S1PR2 were determined using a [ 32 P]S1P competitive binding assay. Out of these new analogues, three compounds, 28c (IC50  = 29.9 ± 3.9 nM), 28e (IC50  = 14.6 ± 1.5 nM), and28g (IC50  = 38.5 ± 6.3 nM) exhibited high binding potency toward S1PR2 and high selectivity over the other four receptor subtypes (S1PR1, 3, 4, and 5; IC50  > 1000 nM). Each of the three potent compounds28c, 28e, and28g contains a fluorine atom that will allow to develop F-18 labeled PET radiotracers for imaging S1PR2.